Ensino de arte: concepções subjacentes às práticas e sua contribuição no processo de emancipação humana - Castro, Uelinton [UNESP] (2015)
This research advances a theme that develops from a contradiction. Whereby the public school instructor in a capitalist society is called upon to act as both provider of human emancipation and producer of alienated training for capitalist propagation. Assuming that the arts discipline plays a key role in human development beyond everyday life, because of its ability to raise the cultural level of students and to develop their aesthetic sensitivity, using the art work produced throughout history. We seek to deduce the teaching practices of Art elementary school teachers epistemological affiliations and through a literature review compares them to art teaching concepts that influenced the art education in Brazil from the Empire to the present day. Thus, this research can contribute to a reflection on the pedagogical practices of the Art teachers, for the development of art discipline as epistemic and the purposes to be achieved in the context of human emancipation